Analysis of the Impact of the Covid-19 Pandemic on Traffic Volume and Revenue at PT. Jasa Marga Belmera Branch - Habil Mirza Hawari; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
The pandemic situation causes uncertainty in various lines of life, including the economic and transportation sectors, including PT. Jasa Marga Belmera branch. With the policy that the government has set through Large-Scale Social Restrictions or the Enforcement of Restrictions on Community Activities, it causes a decrease in community mobility in traveling so that toll road users decrease sharply. Therefore, this study aims to determine the impact caused by the covid-19 pandemic on the traffic volume and income received by the company, and how the strategy carried out by PT. Jasa Marga in dealing with problems related to this matter. The research method used is descriptive qualitative approach. With data obtained through observation, documentation and interviews with staff or employees who work at PT. Jasa Marga Belmera branch. The results showed that the pandemic caused a decrease in vehicle volume by 12.12% and a decrease in income by 8.82%. The strategies used are cost reduction analysis, differentiation analysis and focus analysis. This strategy is carried out so that the company continues to run effectively and efficiently even in a pandemic like now.